2021
DOI: 10.3390/vaccines9060591
|View full text |Cite
|
Sign up to set email alerts
|

Outbreak of SARS-CoV-2 Lineage 20I/501Y.V1 in a Nursing Home Underlines the Crucial Role of Vaccination in Both Residents and Staff

Abstract: Elderly residents in nursing homes are at very high risk of life-threatening COVID-19-related outcomes. In this report, an epidemiological and serological investigation of a SARS-CoV-2 outbreak in an Italian nursing home is described. Among the residents, all but one (19/20) were regularly vaccinated against SARS-CoV-2. In mid-February 2021, a non-vaccinated staff member of the nursing home was diagnosed with the SARS-CoV-2 infection. Following the outbreak investigation, a total of 70% (14/20) of residents ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 35 publications
(38 reference statements)
0
15
0
Order By: Relevance
“…We checked the publication status on 14 March and all remained as preprints [ 61 , 62 , 88 , 169 , 171 ]. The review period from 1 January 2021 onwards includes 52 publications, 3 of which collected data during the period when the alpha variant of concern [ 85 , 125 , 133 ] had been described and vaccines were being introduced.…”
Section: Resultsmentioning
confidence: 99%
“…We checked the publication status on 14 March and all remained as preprints [ 61 , 62 , 88 , 169 , 171 ]. The review period from 1 January 2021 onwards includes 52 publications, 3 of which collected data during the period when the alpha variant of concern [ 85 , 125 , 133 ] had been described and vaccines were being introduced.…”
Section: Resultsmentioning
confidence: 99%
“…We checked the publication status on 14 March 2022 and all were still preprints [61,62,88,169,171]. The review period from 1 January 2021 onwards includes 52 publications, three of which collected data during the period when the alpha variant of concern [85,125,133] had been described and vaccines were being introduced.…”
Section: Resultsmentioning
confidence: 99%
“…Amongst all 130 included studies, 88 studies used more than one method of follow-up to ascertain asymptomatic status (Table 1, S2 Table). Only 22 of 130 studies reported the median or mean age [38,47,70,76,77,83,85,95,99,119-121,124,126,128,133,134,139,143,146,152,164] and only five studies included children only [65,67,110,115,118]. Only 31 studies reported the sex of people with asymptomatic SARS-CoV-2 (Table 1, S2 Table) [38,47,51,53,70,71,75,76,83,85,95,99,107,119-122,124,126,128,133,134,139,143,146,147,150,153,158,162,164].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations